Morphological and Biometrical Study on the Hypophysis Cerebri of Gaddi Goat in Different Seasons - Rao, Arjun Kumar; Pathak, V; Rajput, R; Gupta, D; Shukla, P (Indian Journal of Veterinary Anatomy, 2024)
The present study documents the gross morphological and biometrical characteristics of the pituitary gland in the Gaddi doe. The pituitary glands were collected during different seasons of the year. The year was divided in 5 seasons viz, winter, spring, summer, monsoon, and autumn. Biometric measurements such as length, breadth, thickness, volume, and weight of pituitary gland were measured. The inter-peduncular fossa of the brain contained the pituitary gland of the Gaddi goat, which was a light grey in colour. The pituitary was elongated oval or pyriform-shaped gland. The gland was attached to the ventral surface of the hypothalamus between the optic chiasma in front and the mamillary body in back and at its rosto-dorsal extremity by the infundibular stem. Pituitary relies in large part on the sella turcica of the sphenoid bone. The diaphragm sellae, a fold of duramater, covered it on all sides. The foramen diaphragmaticus, a tiny orifice in the centre of the sella was located on the dorsal side from where the infundibular stem passed. The pituitary gland had a large, rounded caudal portion and an irregularly conical cranial portion with a flattened end. The length, width, thickness, weight and volume of the gland increased significantly towards the breeding season of year. The variance in morphometrical data suggested that the pituitary gland was most active during breeding season (autumn) from September to November.